2021
DOI: 10.1177/11779322211055892
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value Estimation of BRIP1 in Breast Cancer by Exploiting Transcriptomics Data Through Bioinformatics Approaches

Abstract: BRIP1 (Breast Cancer 1 Interacting Helicase 1) is a tumor suppressor gene that has vital function in preserving the genetic stability by repairing DNA damage though have significant associations with the onset of breast cancer (BC) if mutated or overexpressed. In this study, the prognostic value of BRIP1 gene was evaluated and validated through bioinformatics approaches utilizing transcriptomic (mRNA expression) data from several BC databases. To determine the prognostic value, the expression level of mRNA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
0
11
1
Order By: Relevance
“…Whether it be OS, DSS, DFI, or PFI, BRIP1 remained as a high-risk factor in KIRP and PAAD. Although our results from TCGA database did not fnd a correlation between BRIP1 expression and prognosis of breast cancer patients, a study based specifcally on several breast cancer databases exhibited that higher BRIP1 expression was correlated with poor OS, DSS, DFI, and PFI [25]. Another study mining data of LUAD patients from the Genomic Data Commons (GDC) Data Portal indicated that BRIP1 might regulate fbroblast growth factor 22 and afect MAPK as well as Rap 1 signalling pathways in all tumor stages of LUAD, and a high level of BRIP1 showed boundary signifcance on OS [26], in consistence with our results.…”
Section: Discussioncontrasting
confidence: 77%
“…Whether it be OS, DSS, DFI, or PFI, BRIP1 remained as a high-risk factor in KIRP and PAAD. Although our results from TCGA database did not fnd a correlation between BRIP1 expression and prognosis of breast cancer patients, a study based specifcally on several breast cancer databases exhibited that higher BRIP1 expression was correlated with poor OS, DSS, DFI, and PFI [25]. Another study mining data of LUAD patients from the Genomic Data Commons (GDC) Data Portal indicated that BRIP1 might regulate fbroblast growth factor 22 and afect MAPK as well as Rap 1 signalling pathways in all tumor stages of LUAD, and a high level of BRIP1 showed boundary signifcance on OS [26], in consistence with our results.…”
Section: Discussioncontrasting
confidence: 77%
“…105 Huntington disease, Alzheimer disease, Hypoxic Ischemic Encephalopathy, Parkinson disease, and ischemic stroke have all been identified to have aberrant miR-124 expression. 106,107 Our findings revealed that decreased expression of miR-29a and hsa-miR-29b is a prevalent occurrence in many neurodegenerative disorders, including HD 85 and Alzheimer disease 108 and hsa-miR-16 is also a potential miRNA for HD. 109 Differentially expressed genes were then investigated further to understand more about the prospective interactions using minor candidate drugs that could cure HD.…”
Section: Discussionmentioning
confidence: 67%
“…BRCA1 and BRCA2 are required for maintaining chromosomal stability to protect the genome from damage and to transcriptionally regulate some of the genes involved in DNA repair ( Yoshida and Miki, 2004 ). BRIP1 interacts with numerous proteins associated with the regulation of DNA damage responses and signal checkpoints which are vital for retaining chromosomal and genomic constancy ( Khan and Khan, 2021 ). ZBTB1 is a critical upstream regulator of translesion DNA synthesis and promotes chromatin remodelling and translesion DNA for DNA repair ( Kim et al, 2014 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%